Serum zinc levels in children with simple febrile seizure - Singh, Vandana; Yadav, Daksh (Indian Journal of Child Health, 2018)
Background: It has been postulated that children with low serum zinc level are more prone to febrile seizures. Objectives: The objectives of this study were to compare the serum zinc levels in children suffering from febrile seizures with the children with febrile illness without seizures and children with no seizure and fever. Materials and Methods: A prospective case–control study was conducted in the Department of Pediatrics, in a Medical Institution of Meerut, over a period of 2 years (March 2015–May 2017). A total of 150 candidates of age 6 months–60 months were recruited from the pediatric wards and were divided into three subgroups. Group A consisted of 50 children who neither had fever nor seizures. Group B consisted of 50 children who had fever but no seizures. Group C consisted of 50 children who suffered from simple febrile seizure. Here, the Groups A and B served as control while Group C was taken as case. Serum zinc level was assessed in each child after taking written consent from parents. Further, the value of serum zinc was compared among the group. The results were statistically analyzed using the Statistical Package for the Social Sciences Version 21.0 statistical analysis Software. Results: Of 50 children with febrile seizures, 29 (58%) were male. Mean serum zinc levels of all the children included in the study were low (55.42 ?g/dl) as compared to the reference values. There was no significant difference in the serum zinc levels in the febrile seizure group and control groups. Conclusion: We found that the serum zinc level was not associated with febrile seizures.